Molecular Basis for the Therapeutic Effects of Exercise on Mitochondrial Defects - Memme, Jonathan M.; Hood, David A. (Frontiers in Physiology, 2021)
Mitochondrial dysfunction is common to many organ system disorders, including skeletal muscle. Aging muscle and diseases of muscle are often accompanied by defective mitochondrial ATP production. This manuscript will focus on the pre-clinical evidence supporting the use of regular exercise to improve defective mitochondrial metabolism and function in skeletal muscle, through the stimulation of mitochondrial turnover. Examples from aging muscle, muscle-specific mutations and cancer cachexia will be discussed. We will also examine the effects of exercise on the important mitochondrial regulators PGC- 1α, SirT1 and Parkin, and summarize the effects of exercise to reverse mitochondrial dysfunction (eg. ROS production, apoptotic susceptibility, cardiolipin synthesis) in muscle pathology. This paper will illustrate the breadth and benefits of exercise to serve as “mitochondrial medicine” with age and disease.